Apraxia Disorder In Psychology of language's web - Avesta Kamal Mahmood (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This research (Apraxia Disorder In Psychology of language's web) is analyzing the disorder from psycholinguistics point of view , it explains many psycholinguistic aspects that involved in this disorder such as working memory(phonological loop), long term memory especially procedural memory and the process which is working with encoding schemas , all definitions are insisting on that Apraxia is a motor speech disorder (Most of the time, the cause is unknown)that makes it hard for children to speak. It can take a lot of work to learn to say sounds and words better. there by all apraxia children in need to Speech-language pathologists since they have diagnosed with SLI (Special language Impairment). From this perspective the research consists on the psycholinguistic process and how they impact speech and make communication more complex. The research consists two parts: The first part describes the disorder from psycholinguistic point of view and the second part covered the practical analytic and testing a case study which taking as a Kurdish language fragment.